Spectrum of endocrine disorders in a hospitalized patient in a Tertiary University Hospital, Nepal - Yadav, G.; Paudel, G.; Gautam, A.; Maskey, R. (Journal of Diabetes and Endocrinology Association of Nepal, 2022)
Background: The epidemiological spectrum of endocrine disorders in hospitalized patients is not much explored in developing countries. Therefore, the spectrum to visualize a complete picture of the endocrine-related disease is still missing. The study aims to find the spectrum of endocrine-related-disorders in a hospitalized patient, characterize demographic variables, and the duration of hospital stay of patients. Methods: This was a retrospective study of medical records of admitted cases between January 2014 to December 2018 in the Medicine Ward of BPKIHS. Records were retrieved from the Medical office and were entered into Excel and then transferred to SPSS and were analysed. Result: Out of 26,590 admitted cases,1141 (4.3%) had endocrine-related-disease. This includes 565 males and 576 females (1.02: 1 ratio) with an overall mean age of 52.81 ± 16.21 years and median (IQR) age 53 (42-64) years. Among which 904 (79.2%) had Diabetes mellitus, 118 (10.3%) had Metabolic Disorders, 38 (3.3%) had Disorders of Thyroid gland, 38 (3.3%) had Other Nutritional Deficiencies, 29 (2.5%) had Disorders of other endocrine glands, 7 (0.6%) had other disorders of glucose regulation and pancreatic internal secretion, 5 (0.4%) had Overweight, obesity and other hyperalimentation, 2 (0.2%) had Malnutrition. Conclusion: Diabetes and Metabolic disorders are the main components of the spectrum of endocrine disorders in admitted cases. Emphasizing the resources essential for further investigation will help both in dealing with and managing the cases of endocrine disorders.